Síntese e caracterização de perovskitas do tipo TR(FexV1-x)O3(TR=La - Er,Y) - Ivashita, Flávio Francisco (2010)
Metastable perovskites of the TR(FexV1-xO3) type (with TR = La - Er, Y) were synthesized by rapid solidification and characterized structurally, magnetically and regarding the hyperline properties by X-ray diffraction, transmission electron microscopy, magnetometry and Mössbauer spectroscopy. These solid solutions crystallize with the orthorhombic symmetry (Pbnm) and iron and vanadium cations se randomly distributed throughout the octahedral sites of the perovskite structure. For the most studied composition (i.e., X = 0.50), the lattice parameters of these compounds closely follow the lanthanide contraction and groups of two or three "orthoferrivanadates" - as they were hereby baptized - present similar dependence on the magnetization on the temperature. The magnetic behavior for any of these systems is very complex, although all of them reveal, close to the room temperature, a transition between ordered and not-ordered magnetic states. The co-existence of iron and vanadium in the same perovskite lattice retains simultaneously some of the magnetic properties of orthoferrites and orthovanadates, in a combined effect that depends on the TR. Also depending on the lanthanide composing the perovskite, the iron cations can be present with two valences (i.e., Fe2+ and Fe3+). At 85 K, the ferric cations occupy two magnetically different sites, indicating that a phase transition takes place decreasing the temperature. This transition is attributed to an orbital ordering of the type frequently revealed for orthovanadates.